TEACHING ARGUMENTATION IN RURAL CONTEXTS THROUGH DIDACTIC SEQUENCES: EXPERIMENTATION OF THE DIDACTIC DEVICE IN SPANISH - Rodríguez Hernández, Blanca Araceli; Servín Calvillo, Oscar Osvaldo (Revista de Letras, 2022)
Prior research shows the impact of early teaching of argumentation in at least two areas: civic formation and academic success. However, the right to early teaching of critical reading and writing skills becomes a disadvantage for populations living in rural contexts. The objective of this article is to show the effect of a didactic sequence based on the argumentative textual genre on the textual productions of telesecundaria students. As a methodological tool, we take up the didactic sequence based on the textual genre. It has been used in different parts of the world for language teaching. Regarding Spanish, in Mexico, its effectiveness has been explored with textual genres that involve argumentation. This paper shows that students improve overall organization and textual cohesion in final productions and improve their knowledge of the topic of discussion.